ANALISIS PENDAPATAN UNIT USAHA KULINER DI KAWASAN WISATA PANTAI NATSEPA: (Studi Kasus Terhadap Pedagang Rujak Dan Es Kelapa Muda Di Kawasan Pantai Natsepa, Desa Suli, Kabupaten Maluku tengah) - Malissa Indri Batuwael; Merryl Pelamonia; Stevie Sahusilawane (Jurnal Administrasi Terapan, 2022)
This study aims to analyze the income of the Culinary Business Unit in the Natsepa Beach Tourism Area. Respondents in this study were 6 culinary business units in the Natsepa beach tourist area. The data collection technique in this study was a questionnaire, the analytical technique used in this study was ratio analysis. The results showed that the amount of production revenue was Rp. 1,333,333, while the total costs incurred by the budget business owner was Rp. 345,347, the total income earned by each owner of the Rujak, Kelapa Muda and Es Kelapa Muda business in one week was Rp. 987,986/week. Key Word: Income , Culinary Business Unit